Hvordan kan man lære lederskab - Helth, Poula (Academic Quarter | Akademisk kvarter, 2013)
This article focuses on knowledge about learning processes based on a research project where leaders make experiments in order to create new aspects of leadership. Based on movement seeing and the affective turn (Massumi 2002) leaders learn to act differently. The sessions in the project are organized as living, sensing, moving experiments where leaders get inspiration from performance theory (Schechner 2003). The project is based on the assumption that too much of the social theory is unprocessual (Massumi 1997) and that leaders therefore have to learn to become more process oriented thorough their professional leadership training i.e. based on a non-representational theory, that is an approach to understanding the world where we to have to look at the how and not the what (Thrift 2008). The project moves the learning focus from a theoretical study to a performing study in close connection with developing the self as an embodied self; it is the self that is based on desire and corporeality (Elliot 2012). New forms of leadership will occur and we will have to reconsider our traditional ways of organizing educational systems that are often focused on effects and transfer.